Potential problems of public information kiosks. - Chong, Jazmin; Seva, Rosemary
Public information kiosks play an important role in the lives of people as they access relevant information and make important transactions. The objective of the study is to identify possible user problems of public information kiosks to ensure its effectiveness, usability and acceptance among the users. User observation and survey was conducted to two Singapore's public information kiosks. Based on the study conducted, the identified potential problems in general being encountered by users in public information kiosks were speed of processing, poor instruction and interface, usability, accessibility and anthropometric design. These potential problems were due to wrong user mental model and poor physical design.
Keywords: Public information kiosk; Speed of processing; Mental mode; Anthropometric design